2017
DOI: 10.3889/oamjms.2017.158
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of Camel Milk on Poloxamer 407 Induced Hyperlipidaemic Wistar Rats

Abstract: AIM:To investigate the effect of oral administration of camel milk on liver enzymes, total proteins and histology of poloxamer 407 induced hyperlipidaemic wistar rats.MATERIAL AND METHODS:Thirty male wistar rats weighing between 150-200 g were randomly assigned into six groups of five each; group I: administered distilled water, group II: induced with P407, group III: induced with P407 and treated with atorvastatin (20 mg/kg) and groups IV, V and VI: induced with P407 and treated with camel milk 250 mg/kg, 500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“… 2017 ; Zuberu et al. 2017 ). Also, the hypolipidemic effect of camel milk was attributed to its antioxidant potential and the high content of vitamins C and E (Badr et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2017 ; Zuberu et al. 2017 ). Also, the hypolipidemic effect of camel milk was attributed to its antioxidant potential and the high content of vitamins C and E (Badr et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, the major damaging mechanism by which HF-rich diet-induced liver damage, oxidative stress, steatosis, and fibrosis was reported to be due to the activation of the key limiting hepatic enzyme, named fructokinase C (FKC), which catalyses the conversion of fructose to fructose-1-phosphate (F1P) (Vos and Lavine 2013 ; Jegatheesan and De Bandt 2017 ; Zuberu et al. 2017 ). Once hyperactivated, this substrate is sustainedly converted to glucose, fatty acids, lactate, and uric acid to promote hyperglycaemia, hyperlipidaemia, oxidative stress, lipogenesis, and IR (Tappy & Lê 2010 ; Jegatheesan and De Bandt 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…All the groups which were treated with camel milk showed a substantial ( p < 0.05) decrease in the levels of ALT and AST. There is a markable reduction in the levels of total protein content, and globulin in the groups which are given with the camel milk at 250 and 1,000 mg/kg, and there is an increase in the Albumin/Globulin ratio in all the groups that are treated with camel milk ( 41 ).…”
Section: Hepatoprotective Effect Of Camel Milkmentioning
confidence: 99%
“…When the experimental animals are treated with camel milk, NSO alone or its combination may increase the levels of AST, ALT, and ALP and improve the liver toxicity induced by TAA. The results concluded that camel milk, NSO, and camel milk in combination with NSO are effective in correcting toxicity of liver and kidney in rats ( 41 ).…”
Section: Hepatoprotective Effect Of Camel Milkmentioning
confidence: 99%
“…This model has been extensively used in hyperlipidemia research mainly because it produces marked hyperlipidemia (within 24 h) via inhibition of lipoprotein lipase and indirect stimulation of 3-hydroxy-3-methylglutaryl coenzyme A [ 15 , 17 , 20 ]. It should be noted that several reports have shown an absence of poloxamer-induced hepatotoxicity when poloxamer is administered in a single-dose regimen in contrast to the chronic poloxamer 407 model of hyperlipidemia [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. After 1 mg/kg i.p.…”
Section: Introductionmentioning
confidence: 99%